2020
DOI: 10.3389/fmicb.2020.02018
|View full text |Cite
|
Sign up to set email alerts
|

First Cryo-Scanning Electron Microscopy Images and X-Ray Microanalyses of Mucoromycotinian Fine Root Endophytes in Vascular Plants

Abstract: Aims: Arbuscule-producing fine root endophytes (FRE) (previously incorrectly Glomus tenue) were recently placed within subphylum Mucoromycotina; the first report of arbuscules outside subphylum Glomeromycotina. Here, we aimed to estimate nutrient concentrations in plant and fungal structures of FRE and to test the utility of cryoscanning electron microscopy (cryoSEM) for studying these fungi. Methods: We used replicated cryoSEM and X-ray microanalysis of heavily colonized roots of Trifolium subterraneum. Resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 67 publications
(138 reference statements)
0
25
0
Order By: Relevance
“…Such functional complementarity is further supported by the observation that MFRE transfer significant amounts of 15 N but relatively little 33 P tracers to a host lycophyte, Lycopodiella inundata, in the first experimental demonstration of MFRE nutritional mutualism in a vascular plant (Hoysted et al 2019). These results contrast with the majority of studies on MFRE and fine root endophytes (FRE) which have, to date, focussed on the role of the fungi in mediating plant phosphorus (P) acquisition (Orchard et al 2017b, and literature within;Albornoz et al 2020).…”
Section: Introductionmentioning
confidence: 86%
“…Such functional complementarity is further supported by the observation that MFRE transfer significant amounts of 15 N but relatively little 33 P tracers to a host lycophyte, Lycopodiella inundata, in the first experimental demonstration of MFRE nutritional mutualism in a vascular plant (Hoysted et al 2019). These results contrast with the majority of studies on MFRE and fine root endophytes (FRE) which have, to date, focussed on the role of the fungi in mediating plant phosphorus (P) acquisition (Orchard et al 2017b, and literature within;Albornoz et al 2020).…”
Section: Introductionmentioning
confidence: 86%
“…MFRE, within Endogonales (Mucoromycotina, Mucoromycota), are recognized as phylogenetically (Bidartondo et al ., 2011; Spatafora et al ., 2016; Orchard et al ., 2017b) and functionally (Field et al ., 2015, 2019; Hoysted et al ., 2019) distinct from the more commonly studied arbuscular mycorrhizal fungi (AMF), which belong to the Glomeromycotina (or Glomeromycota) (Spatafora et al ., 2016). Research using isotope tracers has shown that MFRE exchange both phosphorus and nitrogen for plant‐fixed carbon when in association with liverworts (Field et al ., 2015, 2016, 2019) and with the vascular plant Lycopodiella inundata (Hoysted et al ., 2019, 2021b), while a cryo‐scanning electron microscopy (SEM) and X‐ray microanalysis study suggests MFRE may play a role in phosphorus assimilation in Trifolium subterraneum (Albornoz et al ., 2020). Where it has been measured, MFRE have been shown to transfer a significant amount of nitrogen to their host plant (Field et al ., 2016, 2019; Hoysted et al ., 2019, 2021a), suggesting that there may be a complementary role for these fungal symbionts alongside AMF.…”
Section: Mucoromycotina ‘Fine Root Endophytes’ Form Globally Widespread Nutritional Mutualisms With Plantsmentioning
confidence: 99%
“…Inoculum production through soil sieving (Gerdemann & Nicolson, 1963; An et al ., 1990; Orchard et al ., 2017b) is currently the only published technique for colonizing experimental vascular plants with MFRE, while excluding the other arbuscule‐forming symbionts, AMF (Albornoz et al ., 2020). This method, based on the observation that AMF spores appear to be much larger than those produced by MFRE, involves wet‐sieving soil collected from a site known to contain MFRE to obtain the material that accumulates between sieves of pore sizes 200 µm and 50 µm.…”
Section: Soil Sievingmentioning
confidence: 99%
See 2 more Smart Citations